2018
DOI: 10.1016/j.apenergy.2018.08.125
|View full text |Cite
|
Sign up to set email alerts
|

Humidification strategy for polymer electrolyte membrane fuel cells – A review

Abstract: Polymer electrolyte membrane fuel cells are promising power sources because of their advantage such as high efficiency, zero emission and low operating temperature. Water management is one of the critical issues for polymer electrolyte membrane fuel cells and has received significant attention. The membrane within the cells needs to stay in hydrated state to have high ion conductivity and durability, which requires proper humidification. Both internal and external methods have been utilized to humidify the pol… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
50
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 163 publications
(57 citation statements)
references
References 116 publications
0
50
0
Order By: Relevance
“…Although there are numerous ways to humidify the cell but still bubble humidifier (passing the reactant gases through a hot water bath before they reach the inlet of the cell) is predominantly used for research purpose due its simple operation. Unlike in PEMFC humidification is required only to hydrate the membrane while in AEMFC humidification is necessary to hydrate the AEM and to provide adequate water for ORR at the cathode [154].Hence selecting a proper humidification strategy is a key to achieve desired performance in AEMFC. A part of water carried to cathode is being utilized in ORR, transported electro osmotically to anode and the excess water is removed through gas exhaust.…”
Section: Effect Of Relative Humiditymentioning
confidence: 99%
“…Although there are numerous ways to humidify the cell but still bubble humidifier (passing the reactant gases through a hot water bath before they reach the inlet of the cell) is predominantly used for research purpose due its simple operation. Unlike in PEMFC humidification is required only to hydrate the membrane while in AEMFC humidification is necessary to hydrate the AEM and to provide adequate water for ORR at the cathode [154].Hence selecting a proper humidification strategy is a key to achieve desired performance in AEMFC. A part of water carried to cathode is being utilized in ORR, transported electro osmotically to anode and the excess water is removed through gas exhaust.…”
Section: Effect Of Relative Humiditymentioning
confidence: 99%
“…A study [47] reported that AEMFCs exhibit improved performance and high stability in 2018. In 2019, numerous reviews of PEMFCs were published, including a review of PEMFC-based micro-combined heat and power systems [48], PEMFC applications for electric vehicles and energy management strategies [49,50], PEMFC poisoning by contaminants and impurities [51], mechanical compression effects and stress effects on PEMFCs [52,53], humidification strategy for PEMFCs [54], and design optimization for PEMFCs [55]. These reviews are similar to the 2000 reviews of SOFCs.…”
Section: Technology Review Of Fuel Cellsmentioning
confidence: 99%
“…For example, for portable or vehicle applications, internal humidification may be preferable to reduce weight and space; while for stationary applications, sufficient humidification performance becomes more important, thus gas bubbling humidification or direct water injection method is more preferable. More details on FC humidification strategy can be found in the review paper [53].…”
Section: Auxiliary Components Performance Improvementmentioning
confidence: 99%